Virtual Reality Instruction Followed by Enactment Can Increase Procedural Knowledge in a Science Lesson - Andreasen, Niels Koch; Baceviciute, Sarune; Pande, Prajakt; Makransky, Guido (Proceedings (IEEE Conference on Virtual Reality and 3D User Interfaces. Online), 2019)
A 2×2 between-subjects experiment (a) investigated and compared the instructional effectiveness of immersive virtual reality (VR) versus video as media for teaching scientific procedural knowledge, and (b) examined the efficacy of enactment as a generative learning strategy in combination with the respective instructional media. A total of 117 high school students (74 females) were randomly distributed across four instructional groups - VR and enactment, video and enactment, only VR, and only video. Outcome measures included declarative knowledge, procedural knowledge, knowledge transfer, and subjective ratings of perceived enjoyment. Results indicated that there were no main effects or interactions for the outcomes of declarative knowledge or transfer. However, there was a significant interaction between media and method for the outcome of procedural knowledge with the VR and enactment group having the highest performance. Furthermore, media also seemed to have a significant effect on student perceived enjoyment, indicating that the groups enjoyed the VR simulation significantly more than the video. The results deepen our understanding of how we learn with immersive technology, as well as suggest important implications for implementing VR in schools.